Human Traffic and Transnational Crime: Eurasian and American Perspectives - Stoecker, Sally; Shelley, Louise (Rowman & Littlefield Publishers, 2004)
Human Trafficking is a growing transnational criminal phenomenon_conservative estimates put the total number of persons trafficked annually at two million. In this first in-depth study of human trafficking in Russia and Ukraine, scholars from the European, Siberian, and far-eastern parts of Russia offer groundbreaking analyses of the motivations behind and reactions to this horrifying trend.